Análise da percepção de desconforto em diferentes regiões dos pés - Menin, Mariana [UNESP]; Silva, José Carlos Plácido da [UNESP]; Paschoarelli, Luis Carlos [UNESP] (My University, 2010)
The comfort is is an important feature for acquiring shoes. Matching this product to the characteristics of their customers is one of the requirements for a comfortable shoe. In this study, there were evaluated the discomfort perception in different parts of the feet by obese and nonobese volunteers.

O conforto é um atributo importante para a aquisição de calçados. Adequar este produto às características de seus usuários é um dos requisitos para um calçado confortável. Neste estudo, foram avaliadas as percepções de desconforto em diferentes regiões dos pés por indivíduos obesos e não obesos.
Keywords: Shoes; Comfort; Ergonomic design; Calçados; Conforto; Design ergonômico